2017
DOI: 10.18203/2320-6012.ijrms20170624
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of haemodynamic effects of lateral and sitting positions during induction of spinal anaesthesia for elective caesarean section

Abstract: Background: Spinal anaesthesia avoids the problems associated with general anaesthesia such as airway manipulation, polypharmacy, postoperative respiratory problems, and cognitive dysfunction. It can be given in lateral and sitting positions. The aim of the present study was to compare the effect of induction position for spinal anaesthesia in elective caesarean section on hemodynamic, sensory and motor block characteristics and patient satisfaction.Methods: 120 ASA physical status I and II patients undergoing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 6 publications
1
3
1
Order By: Relevance
“…In our study, it was found that in sitting position, 53.1% of the patients and in left lateral decubitus position, 40.6% of the patients required ephedrine supplementation but the difference was comparable. The ephedrine requirements were comparable in both sitting and lateral groups as documented by Gómez et al 15 , Arokyamuthu V et al 16 , Kharge et al 17 and Inglis A et al 9 in their respective studies. Coppejans HC et al 18 and Simin A et al 10 evaluated that the females in the sitting group required less ephedrine as compared to lateral group.…”
Section: Sensory Block Characteristicssupporting
confidence: 72%
“…In our study, it was found that in sitting position, 53.1% of the patients and in left lateral decubitus position, 40.6% of the patients required ephedrine supplementation but the difference was comparable. The ephedrine requirements were comparable in both sitting and lateral groups as documented by Gómez et al 15 , Arokyamuthu V et al 16 , Kharge et al 17 and Inglis A et al 9 in their respective studies. Coppejans HC et al 18 and Simin A et al 10 evaluated that the females in the sitting group required less ephedrine as compared to lateral group.…”
Section: Sensory Block Characteristicssupporting
confidence: 72%
“…12 Ramayyan et al found that hemodynamic stability was more in the sitting position whereas Kharge et al found no significant difference in hemodynamic parameters in the two positions but the participants seemed more comfortable in the lateral position (p< 0.001). 9,13 In this study we could not find significant difference in the time to reach sensory block level to T6 in the sitting versus left lateral positions (3.97±0.94 min; 4.05±0.90 min; p=0.57). Though one of our earlier study found the onset to be faster in the lateral position, the insignificant finding might result from adjustment in table position by the attending anaesthesiologist.…”
Section: Discussioncontrasting
confidence: 55%
“…The medical sympathectomy after spinal anesthesia increases gravity-induced peripheral blood pooling, which usually leads to significant hypotension. The lateral recumbent position causes less hypotension compared to the sitting position [9].…”
Section: Discussionmentioning
confidence: 94%